Fertilization in Eucalyptus grand1s on Severely Truncated Soil. I: Growth Studies - Prasad, K. G.; Kumar, Dnesh; Chandrashekharan Nair, T. J.; Mohan, S.; Madav Nair, J.; Deo, A. D. (Indian Forester, 1984)
A factorial experiment with four levels (0.25, 50 and 75 g/plant) eacb of Urea and Superphosphate was carried out witb E. grandis grown on a severely truncated (Lithic Dystropept) soils at Minmutti, Idukki District, Kerala. Height, collar circumference, crown diameter and volume of E. grandis plants Increased with the application of N ferlilizer alone or in combination with P. However, P application alone was inferior to control treatment. Considering tbe growth parameters, relative treatment elfecllveness (RTE) and relative economic effecliveness (REE), treatment N75 P75 was the best followed by N75 P50 and N50 P75 treatments.